Mitochondrial fusion is a therapeutic vulnerability of acute myeloid leukemia - Clément Larrue; Sarah Mouche; Shan Lin; Federico Simonetta; Nastassja K. Scheidegger; Laury Poulain; Rudy Birsen; Jean‐Emmanuel Sarry; Kimberly Stegmaier; Jérôme Tamburini (2023)
Abstract Mitochondrial metabolism recently emerged as a critical dependency in acute myeloid leukemia (AML). The shape of mitochondria is tightly regulated by dynamin GTPase proteins, which drive opposing fusion and fission forces to consistently adapt bioenergetics to the cellular context. Here, we showed that targeting mitochondrial fusion was a new vulnerability of AML cells, when assayed in patient-derived xenograft (PDX) models. Genetic depletion of mitofusin 2 (MFN2) or optic atrophy 1 (OPA1) or pharmacological inhibition of OPA1 (MYLS22) blocked mitochondrial fusion and had significant anti-leukemic activity, while having limited impact on normal hematopoietic cells ex vivo and in vivo. Mechanistically, inhibition of mitochondrial fusion disrupted mitochondrial respiration and reactive oxygen species production, leading to cell cycle arrest at the G 0 /G 1 transition. These results nominate the inhibition of mitochondrial fusion as a promising therapeutic approach for AML.